A proposal for a novel approach to reduce burdens of care for people with dementia: A hypothesis. Issue 2 (15th June 2021) - Varshney, Smita U.; Varshney, Upkar; McCall, William V.
Abstract: Cognitive impairment of dementia patients affects their ability to communicate and cooperate with care. Dementia patients need a specialized communication to increase their cooperation during daily care and a scale to measure cooperation with care. To improve communication, we created and applied a digital communication platform (DCP) in an observational study. To measure cooperation with care, we created and tested psychometric properties of the Cooperation with Care Scale‐Revised (CWCS‐R) in an institutional review board–approved 6‐week prospective study. DCP intervention was associated with decreased agitation and use of psychotropic medications for nursing home (NH) dementia patients. CWCS‐R is both a reliable and valid tool to measure cooperation with care in NH dementia patients. Innovations in communication with dementia patients and a scale to measure cooperation with care could reduce burdens of care and improve quality of life for patients, their family members, and staff. It may potentially help decrease cost of dementia care.